Estimated risks and optimistic self-perception of breast cancer risk in Korean women. - ChaeWeon Chung; Suk Jeong Lee (Applied Nursing Research, 2013)
Aim: To determine women's perceived personal and comparative risks of breast cancer, and to examine the relationships with risk factors. Background: Despite the increasing incidence of breast cancer in younger women and the availability of screening, women's health behaviors have not advanced accordingly. Methods: A cross-sectional survey design utilized a convenience sample of 222 women in their 30s and 40s recruited from community settings in Seoul. Self-administered questionnaire data were analyzed by descriptive statistics, the chi-squared test, and ANOVA. Results: Risk perception levels differed significantly by breast cancer risk factors. Half of the women were optimistic about their breast cancer risk, while perceived personal risk did not reflect women's own risk factors and comparative risk differed only by the practice of clinical breast exam. Conclusions: Women's knowledge and awareness of their breast cancer risk factors need to be improved for appropriate risk perception and health behaviors, and accurate risk estimation could be utilized to educate them in clinical settings.